Trauma e histórico de vitimização na escola: um estudo retrospectivo com estudantes universitários - Albuquerque, Paloma Pegolo de (2014)
School victimization may favor the occurrence of traumatic symptoms and Post Traumatic Stress Disorder (PTSD). This Doctoral Thesis had the following objectives: validate the American retrospective instrument Student Alienation and Trauma Survey - R (SATS-R), to Brazil, in terms of construct and content validity; characterize how violence is expressed at school, identifying the main types of violence, the worst school events experienced by students, the frequency and duration of these events, main perpetrators, as well as victims' characteristics (age, grade and type of school); investigate the occurrence of traumatic symptoms, especially PTSD, after the worst school experience; analyze the association between PTSD symptoms and variables associated with the worst school experience, and investigate the relationship between the explanatory variables (individual characteristics and aversive school experiences), and development of PTSD symptoms, using an ordinal logistic regression model. The study included 691 students (54.8% female and 45.2% male), of a public university in São Paulo State, Brazil, who responded to Portuguese versions of the Student Alienation and Trauma Survey-R (SATS-R) and the Post-Traumatic Stress Disorder Checklist - Civilian Version (PCL-C). In terms of content validity, the following procedures were conducted: translation, back-translation, semantic equivalence, instrument analysis by experts in the field, and a sample assessment of the target population; for construct validity, an exploratory factor analysis was conduct and Cronbach's alpha was calculated. The study results indicate the feasibility of using the instrument in the Brazilian context for research purposes. Frequency of victimization types reported by participants were: relational violence (at least one item reported by 85.2%); verbal violence (77.7%); physical violence (50.8%); unfair discipline (43.1%); property violence (33.4%); witnessing violence (27.9%); and sexual violence (21.4%). The most frequent types of worst school experiences described were: relational (35.7%), and verbal violence (27.4%). Girls experienced more episodes of verbal, relational and sexual violence, and boys experienced more physical violence and unfair discipline, and the aggressors were mostly male students. The mean age when these worst experiences occurred was 12.3 years, and although most events occurred at low frequency and with short duration, a considerable percentage of participants indicated a duration of "years", particularly in verbal and relational victimization cases. Most participants indicated that they were greatly bothered by their worst school experience, and 7.8% had PTSD symptons after experiencing this event. The percentage of participants with clinically significant scores on the subscales ranged from 4.7% (somatic symptoms) to 20% (hypervigilance), and described symptoms frequently in the literature, such as depression, hopelessness, cognitive difficulties and traumatic event recollection. Significant variables for the regression model were: age, duration and discomfort after the worst experience; relational violence; and verbal violence. In general, student who expressed the greatest discomfort, reported traumatic experiences that were longer in duration, occured when they were older, and the greater the number of verbal and relational victimization events experienced, the greater the possibility of presenting clinically significant symptoms of PTSD. Despite the limitations of the retrospective methodo, the study obtained interesting results which coincide with the literature, drawing attention to the long-term effects of school victimization. In addition, these results may contribute to the development of new research on the topic, as well as offering treatment parameters for victims who were traumatized in school, improving school violence prevention programs.